Final report and recommendations derived from multi-stakeholder consultations organized by New Rules for Global Finance Coalition November 2004 through September 2005 ([The Coalition] [S.l.], 2005)
Contains New Rule's recommendations of concrete, viable policies for improving the financing of development. Addresses needed changes in the governance of global financial rule-making bodies.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT